Sherlock Holmes [videorecording (Blu-Ray + DVD)] - Zimmer, Hans (Internationale Filmproduktion Blackbird Zweite GmbH & Co. KG, 2009)
After finally catching serial killer and occult 'sorcerer' Lord Blackwood, legendary sleuth Sherlock Holmes and his assistant Dr. Watson can close yet another successful case. After his execution, Blackwood mysteriously returns from the grave and resumes his killing spree, Holmes must take up the hunt once again. Contending with Watson's new fiancée and the dimwitted head of Scotland Yard, the determined detective must unravel the clues that will lead him into a twisted web of murder, deceit, and black magic, not to mention the deadly embrace of temptress Irene Adler.